Rationale book five: commentary on the divine office - Durantis, Guilelmus, Mende, Bischof (Corpus Christianorum in translation, 2015)
"William Durand (c. 1230-Nov. 1, 1296), Bishop of Mende, France, was unquestionably the most renowned liturgical scholar of the later Middle Ages. His encyclopedic allegorical exposition of the rites and worship services of the Latin Church, the Rationale divinorum officiorum, or "Rationale for the divine offices," is the best known medieval work in its genre. Divided into eight books of varying length, the Rationale is exhaustive in its treatment of a wide variety of subjects: the church building and liturgical art; the ministers of the church and their functions; liturgical vestments; the Mass and the Divine Office; the Church's calendar and its feast days. Modern scholarship has clearly shown that Durand's Rationale superseded all previous liturgical commentaries within only a few years of its publication (c. 1292-1296). By the end of the fifteenth century, it had become one of the most widely disseminated treatises of its kind in western Europe."--Publisher description